High-flexibility low-reflection flexible photovoltaic glass and preparation method thereof
Through substrate activation and sandwich structure design, the multi-dimensional contradictions in flexible photovoltaic glass in terms of flexibility, optical performance and environmental stability are solved, and flexible photovoltaic glass preparation with high flexibility, low reflectivity and excellent moisture and heat resistance is achieved.
Patent Information
- Application Number
- CN202510671304.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-22
- Publication Date
- 2025-08-26
AI Technical Summary
Existing flexible photovoltaic glasses are difficult to coordinately balance flexibility, optical properties, environmental stability and mechanical strength, resulting in limited applications in dynamic bending scenarios and complex operating conditions.
Through substrate activation, sandwich structure design and process optimization, including plasma activation treatment, spin-coated perovskite active layer, magnetron sputtering transparent conductive layer, vacuum laminated packaging, coated SiO2 and PVDF layers and nano-silver island-like structure, it forms a comprehensive performance of high flexibility, low reflectivity, excellent moisture and heat resistance and reliable mechanical strength.
The comprehensive performance improvement of high flexibility (recovery rate of 1000 cycle bending with 5mm radius of curvature >95%), low reflectivity (NIR reflectivity >89.3%), high light transmittance (PAR transmittance >92.5%), excellent moisture and heat resistance (reflectivity retention rate after 85°C/85%RH aging) and reliable mechanical strength (adhesion level 4B) is achieved.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic glass preparation, and in particular to a flexible photovoltaic glass with high flexibility and low reflection and a preparation method thereof. Background Art
[0002] With the rapid development of renewable energy technology, flexible photovoltaic glass has shown great application potential in the fields of building-integrated photovoltaics, curved roofs, wearable electronic devices, etc. due to its lightweight and bendable characteristics. Traditional photovoltaic glass is based on a rigid glass substrate. Although it has high light transmittance and weather resistance, its high brittleness and poor flexibility seriously limit its application in dynamic bending scenarios. In addition, photovoltaic modules have increasingly stringent requirements on optical properties (such as transmittance, reflectivity) and environmental stability (such as resistance to moisture and heat, and anti-oxidation). There is an urgent need to develop new flexible photovoltaic materials with high flexibility, excellent optical properties and long-term stability.
[0003] In order to break through the limitations of traditional rigid substrates, existing technologies have attempted to improve the flexibility of photovoltaic glass through various means. One mainstream solution is to use flexible polymers such as polyimide (PI) and polyethylene terephthalate (PET) to replace the glass substrate, and integrate photovoltaic functional layers such as perovskite and amorphous silicon in combination with spin coating or lamination processes. However, this type of polymer substrate has poor temperature resistance (the long-term operating temperature is usually below 150°C), and is prone to aging and degradation under high temperature or long-term ultraviolet radiation, significantly shortening the service life of the device; in addition, the thermal expansion coefficients of the polymer and the inorganic functional layer (such as indium tin oxide electrode) are quite different, and the interface is prone to delamination due to thermal stress accumulation, affecting the reliability of the device. Another type of technical solution focuses on optimizing optical performance, such as coating a single anti-reflection layer such as silicon dioxide (SiO2) or magnesium fluoride (MgF2) on the glass surface to reduce surface reflectivity. However, this type of coating has limited effect in suppressing the reflection of broad-spectrum light (especially the near-infrared band) (the near-infrared reflectivity is still higher than 20%), and the bonding strength between the rigid coating and the flexible substrate is weak, making it prone to cracking or falling off during repeated bending.
[0004] While existing technologies have achieved breakthroughs in some areas, they often suffer from limitations that compromise performance: either sacrificing substrate rigidity for flexibility or optimizing only for a single performance factor (such as anti-reflection). These limitations fail to systematically address the multi-dimensional performance contradictions faced by flexible photovoltaic glass under complex operating conditions. For example, insufficient interfacial bonding between the flexible substrate and the inorganic coating, the difficulty in synergistically optimizing broad-spectrum reflection suppression and high light transmittance, and metal layer oxidation caused by aging of the packaging material in hot and humid environments remain core bottlenecks hindering its commercial application. Summary of the Invention
[0005] The embodiments of the present application provide a highly flexible and low-reflective flexible photovoltaic glass and a preparation method thereof. Through substrate activation, sandwich structure design and process optimization, the problem of the difficulty in balancing flexibility, optical properties, environmental stability and mechanical strength of flexible photovoltaic glass in the prior art is systematically solved. Ultimately, the comprehensive performance improvement of high flexibility (recovery rate of 1000 bending cycles with a curvature radius of 5mm is greater than 95%), low reflectivity (NIR reflectivity is greater than 89.3%), high light transmittance (PAR transmittance is greater than 92.5%), excellent moisture and heat resistance (reflectivity retention rate after aging at 85°C / 85%RH is greater than 96%) and reliable mechanical strength (adhesion grade 4B) is achieved.
[0006] The present invention provides a method for preparing a flexible photovoltaic glass with high flexibility and low reflection, which is characterized by comprising the following steps:
[0007] ① Cleaning and plasma activation treatment of the flexible glass substrate, wherein the plasma activation treatment is specifically performed on the lower surface under an argon atmosphere, with a processing power of 100 W and a processing time of 5 minutes;
[0008] ② Spin-coating the perovskite precursor solution on the substrate pretreated in step ①, annealing the solution on a hot plate at 100°C for 10 minutes to form a perovskite active layer, and then depositing a transparent conductive layer on the surface of the perovskite active layer by magnetron sputtering with a deposition thickness of 100±10nm and a square resistance of 15±2Ω / sq. Then, depositing a metal back electrode on the surface of the transparent conductive layer by thermal evaporation;
[0009] ③ Using EVA material as packaging material, placing the EVA packaging material and the photovoltaic module prepared in step ② in a vacuum laminator for lamination packaging;
[0010] ④ Coating a transition layer on the surface of the encapsulation layer in step ③;
[0011] ⑤ In step ④, the surface of the transition layer is first coated with SiO2 sol by spin coating and cured by ultraviolet light to form an inorganic coating SiO2 layer, and then a PVDF layer is coated on the surface of the SiO2 layer to deposit a nano-silver island structure, and then covered with a second PVDF layer to form a sandwich structure. After the second PVDF layer is coated, the flexible photovoltaic glass is obtained.
[0012] Preferably, the lamination packaging process parameters in step ③ are as follows: temperature 120±2° C., pressure 0.5±0.05 MPa, time 10±0.5 min, vacuum degree ≤100 Pa, and thickness 200±10 μm.
[0013] Preferably, the transition layer in step ④ is specifically an acrylic adhesive, and the spraying process is a pressure of 0.18-0.22 MPa, a distance of 18-20 cm, a thickness of 10±1 nm, and finally cured at room temperature for 23-25 hours.
[0014] Preferably, the coverage of the nanosilver island structure in step ⑤ is 40-50%, and the thickness is 50±5 nm.
[0015] Preferably, the second PVDF layer in step ⑤ is doped with 0.5% antioxidant, and the antioxidant is selected from Irganox 1010.
[0016] The present invention also provides a flexible photovoltaic glass with high flexibility and low reflection, which is prepared by any of the above methods, and its structure includes: a flexible glass substrate, a perovskite active layer, a transparent conductive layer, an EVA encapsulation layer, a transition layer, a SiO2 inorganic coating and a "PVDF / Ag / PVDF" sandwich structure.
[0017] One or more technical solutions provided in the embodiments of this application have at least the following technical effects or advantages:
[0018] 1. Through substrate activation, sandwich structure design and process optimization, the difficult problem of flexible photovoltaic glass in the existing technology that is difficult to coordinate and balance in terms of flexibility, optical properties, environmental stability and mechanical strength has been systematically solved. Finally, the comprehensive performance improvement of high flexibility (recovery rate of 1000 bending cycles with a curvature radius of 5mm is greater than 95%), low reflectivity (NIR reflectivity is greater than 89.3%), high light transmittance (PAR transmittance is greater than 92.5%), excellent moisture and heat resistance (reflectivity retention rate after aging at 85℃ / 85%RH is greater than 96%) and reliable mechanical strength (adhesion grade 4B) is achieved.
[0019] 2. The embodiment of the present invention significantly improves the surface energy of the substrate through argon plasma activation power of 100W for 5 minutes. Combined with an acrylic transition layer with a thickness of 10±1nm and a "PVDF / Ag / PVDF" sandwich structure, the recovery rate is greater than 95% after 1000 cyclic bending cycles at a curvature radius of 5mm, and the NIR reflectivity attenuation is ≤5%, resolving the contradiction between flexibility and interfacial bonding strength.
[0020] 3. In the embodiment of the present invention, a nanosilver island structure (coverage 40-50%, thickness 50±5nm) is combined with a UV-cured SiO2 coating (transmittance >95%) to achieve a PAR transmittance >92.5% and an NIR reflectivity >89.3%. At the same time, the antioxidant Irganox 1010 is embedded in the PVDF layer, so that the reflectivity retention rate is >96% after aging at 85°C / 85% RH for 100 hours, resolving the contradiction between optical performance and stability.
[0021] 4. The embodiment of the present invention uses vacuum lamination packaging at a temperature of 120±2°C and a pressure of 0.5±0.05MPa combined with a nano-silver layer heat dissipation design, which reduces the component operating temperature by 10°C and improves efficiency by 4.2%. The SiO2 coating has a hardness of 4H and an adhesion grade of ASTM D33594B, ensuring long-term reliability and resolving the contradiction between thermal management and mechanical strength. DETAILED DESCRIPTION
[0022] In order to better understand the above technical solution, the above technical solution will be described in detail below in combination with the specification and specific implementation methods.
[0023] Example 1
[0024] (1) An ultra-thin flexible glass substrate with a thickness of 100 μm was selected and cut into a standard size of 1 m × 1 m according to actual application requirements. The cut flexible glass substrate was immersed in acetone, ethanol and deionized water in turn for ultrasonic cleaning. The specific process parameters are as follows: ultrasonic power = 150 W, cleaning time: 15 minutes in each tank of liquid. After cleaning, high-pressure nitrogen was used to purge the residual droplets on the surface of the substrate. The purge pressure was 0.3 MPa to ensure that there was no solvent residue on the surface of the substrate. The dried flexible glass substrate was placed in a low-temperature plasma treatment machine and surface activation treatment was performed under argon atmosphere. The process parameters were as follows: treatment power = 100 W, treatment time = 5 min, working pressure = 50 Pa. After the above treatment, the surface energy of the substrate was increased to ≥ 60 mN / m, significantly enhancing the interface adhesion of the subsequent functional coating.
[0025] (2) Lead iodide (PbI2) and methylamine iodide (MAI) are dissolved in a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 1:1, wherein the volume ratio of DMF to DMSO is 4:1, to prepare a perovskite precursor solution. The precursor solution is applied to the surface of a pretreated flexible glass substrate by spin coating, and the spin coating process parameters are as follows: rotation speed = 4000 rpm per minute, time = 30 s, and preferably acceleration 2000 rpm / s. The spin-coated substrate is placed in a nitrogen atmosphere and annealed on a hot plate at a temperature of 100°C for 10 minutes to form a perovskite active layer with a thickness of 500±20 nm. A transparent conductive layer of indium tin oxide (ITO) was deposited on the surface of the perovskite active layer by magnetron sputtering. The process parameters were as follows: the target material was an indium tin oxide target, the sputtering power was 150 W, the working pressure was 0.5 Pa, the deposition thickness was 100 ± 10 nm, and the square resistance was 15 ± 2 Ω / sq. A metal back electrode was deposited on the surface of the transparent conductive layer by thermal evaporation. The material was silver (Ag) or aluminum (Al), and the deposition thickness was 150 ± 10 nm.
[0026] (3) Ethylene-vinyl acetate copolymer (EVA) is selected as the packaging material for flexible photovoltaic glass. The vinyl acetate content of the EVA material is 28-33wt% and the melt index is 25-30g / 10min (test conditions: 190°C, 2.16kg). The EVA packaging material and the photovoltaic module prepared in step (2) are placed in a vacuum laminator for lamination packaging. The specific process parameters are as follows: temperature = 120±2°C, pressure = 0.5±0.05MPa, time = 10±0.5min, vacuum degree ≤100Pa, thickness 200±10μm. After lamination is completed, it is naturally cooled to room temperature to obtain a photovoltaic module with a complete packaging structure. The precisely controlled temperature-pressure-time parameters work together to ensure that the EVA is fully cross-linked, so that the EVA material is fully cross-linked to form a stable three-dimensional mesh packaging protective layer.
[0027] (4) Apply an acrylic adhesive to the surface of the encapsulation layer using the following spraying parameters: pressure = 0.18-0.22 MPa, distance = 18-20 cm, thickness 10 ± 1 nm, and then cure at room temperature for 23-25 hours. Apply an acrylic adhesive transition layer to enhance the interfacial adhesion between the encapsulation layer EVA and the subsequent SiO2 inorganic coating. The transition layer must have chemical affinity with both the photovoltaic encapsulation materials EVA and PVDF.
[0028] If the adhesion is insufficient, the thickness of the transition layer can be increased to 20 nm, or plasma treatment can be used to enhance the surface activity.
[0029] (5) Add 20.8 g of ethyl orthosilicate and 18.4 g of anhydrous ethanol to a beaker. Slowly add a mixed solution consisting of 1.89 g of deionized water and 8 drops of hydrochloric acid under constant temperature magnetic stirring. Stir at room temperature for 4.5 h, then add 0.2 g of a photoinitiator such as Irgacure 184. Stir for another 0.5 h to form a SiO2 sol. The sol can be stored stably for more than 24 hours with a viscosity change rate of <5%.
[0030] Adding the photoinitiator too early (e.g., after 2 hours) can cause partial crosslinking of the sol, resulting in a sudden increase in viscosity (viscosity > 200 cP). Adding the photoinitiator too late (e.g., after 5 hours) can cause the sol to gel and the photoinitiator to disperse unevenly. Experiments have shown that adding the photoinitiator after 4.5 hours can achieve a UV-cured coating with a pencil hardness of 4H and a transmittance > 95%.
[0031] Add 0.04g of a surfactant, such as Triton X-100, to the SiO2 sol to reduce the surface tension of the sol and minimize coating defects. Spin coat the sol onto the flexible photovoltaic glass after the transition layer is applied in step (4) with a thickness of 100μm. Spin coating parameters: 3000rpm, 30s. Allow the sol to spread evenly for 10s before spin coating. Initiate crosslinking by UV light to avoid high temperature treatment. UV light curing parameters: UV wavelength 365nm, irradiation intensity 10mW / cm 2 , and cured for 5 minutes to form an inorganic SiO2 coating with a thickness of 50±5nm and a surface roughness of <2nm.
[0032] First, prepare a DMF / acetone mixed solvent at a volume ratio of 7:3. Dissolve 0.9g of PVDF powder in 11.1g of the DMF / acetone mixed solvent to prepare a PVDF solution. Stir the resulting mixture at 40°C for 1 hour to form a colorless, transparent solution. The PVDF solution is then spin-coated onto the inorganic SiO2 coating using the following process parameters: spin speed = 2000 rpm, spin coating time = 20 seconds, thickness = 30±5nm. After coating, the coating is annealed at 80°C for 10 minutes. This annealing not only eliminates residual solvent but also increases the PVDF crystallinity from 45% to 60% (DSC test), enhancing mechanical strength without compromising light transmittance. After drying, the PVDF layer is formed.
[0033] A nanosilver layer was deposited on a polyvinylidene fluoride (PVDF) layer using magnetron sputtering. The process parameters were: a high-purity Ag target (99.99%), a DC power of 80W, an argon flow rate of 25sccm, an operating pressure of 0.8Pa, a substrate temperature of ≤50°C, and a sputtering time of 3 minutes. This resulted in an island structure with a thickness of 50±5nm (coverage of 40-50%) to reduce visible light reflection. A second layer of polyvinylidene fluoride (PVDF) solution was then applied by spin coating using the same spin coating and annealing parameters as the first PVDF layer. After annealing, the layer was immediately cooled under a nitrogen atmosphere at a cooling rate of ≤2°C / min. The surface roughness was maintained at <3nm after annealing, ultimately forming a "PVDF / Ag / PVDF" sandwich structure. After the second PVDF layer was applied, flexible photovoltaic glass was produced.
[0034] Among them, the island structure coverage can be monitored in real time through SEM to ensure the balance of optical and electrical performance.
[0035] Wherein, 0.5% (based on the mass of the polyvinylidene fluoride PVDF solution) of an antioxidant (such as Irganox 1010) is added to the second layer polyvinylidene fluoride PVDF solution to delay oxidation of the silver layer.
[0036] (6) Post-processing and performance verification of flexible photovoltaic glass,
[0037] The test conditions are as follows: curvature radius = 5 mm, number of cycles = 1000 times.
[0038] Test results: recovery rate>95%, NIR reflectivity attenuation≤5%.
[0039] Optical performance testing equipment: UV-visible-near-infrared spectrophotometer (PerkinElmer Lambda950).
[0040] Test results: PAR transmittance (400-700nm)>92.5%. NIR reflectivity (700-2500nm)>89.3%.
[0041] Thermal management test conditions: outdoor light intensity = 1000W / m 2 , lasting 8 hours.
[0042] Test results: The operating temperature of the components decreased by 10°C and the efficiency increased by 4.2%.
[0043] Environmental stability test conditions: 85°C / 85% RH, aging for 100 hours.
[0044] Test results: NIR reflectivity retention rate > 96%. Oxidation spot coverage rate < 3%.
[0045] Adhesion Grade: ASTM D33594B.
[0046] Comparative Example: Preparation method of traditional polymer-based flexible photovoltaic glass
[0047] (1) A polyimide (PI) film (thickness 100 μm) was used to replace the flexible glass substrate and ultrasonic cleaning was performed only with ethanol (power 150 W, 15 min) without plasma activation.
[0048] (2) The same perovskite precursor solution as in Example 1 was spin-coated, and the annealing conditions (100° C., 10 min) were consistent with those in Example 1 of the present invention to deposit an ITO transparent conductive layer (thickness 100±10 nm).
[0049] (3) EVA lamination packaging (temperature 120 °C, pressure 0.5 MPa) was used to coat a single SiO2 anti-reflection layer (thickness 50 nm) without a transition layer and sandwich structure to produce a traditional polymer-based flexible photovoltaic glass.
[0050] Comparison of technical effects between Example 1 of the present invention and the comparative example
[0051]
[0052]
[0053] Conclusion: Due to the lack of substrate activation treatment, transition layer installation, and "PVDF / Ag / PVDF" sandwich structure design, the performance indicators of the comparative example of the present invention are significantly lower than the technical results achieved by Example 1 of the present invention. Comparative experimental data clearly demonstrates that Example 1 of the present invention, through specific process innovations including but not limited to substrate activation treatment, transition layer installation, and sandwich structure design, significantly contributes to improving the overall performance of flexible photovoltaic glass. This comparative result fully demonstrates the necessity and synergistic effect of each key process step in the technical solution of the present invention.
[0054] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0055] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.
Claims
1. A method for preparing highly flexible and low-reflective flexible photovoltaic glass, characterized in that: The following steps are involved: ① Cleaning and plasma activation treatment of the flexible glass substrate, wherein the plasma activation treatment is specifically performed on the lower surface under an argon atmosphere, with a processing power of 100 W and a processing time of 5 minutes; ② Spin-coating the perovskite precursor solution on the substrate pretreated in step ①, annealing the solution on a hot plate at 100°C for 10 minutes to form a perovskite active layer, and then depositing a transparent conductive layer on the surface of the perovskite active layer by magnetron sputtering with a deposition thickness of 100±10nm and a square resistance of 15±2Ω / sq. Then, depositing a metal back electrode on the surface of the transparent conductive layer by thermal evaporation; ③ Using EVA material as packaging material, placing the EVA packaging material and the photovoltaic module prepared in step ② in a vacuum laminator for lamination packaging; ④ Coating a transition layer on the surface of the encapsulation layer in step ③; ⑤ In step ④, the surface of the transition layer is first coated with SiO2 sol by spin coating and cured by ultraviolet light to form an inorganic coating SiO2 layer, and then a PVDF layer is coated on the surface of the SiO2 layer to deposit a nano-silver island structure, and then covered with a second PVDF layer to form a sandwich structure. After the second PVDF layer is coated, the flexible photovoltaic glass is obtained.
2. The preparation method according to claim 1, characterized in that The lamination packaging process parameters in step ③ are specifically: temperature 120±2° C., pressure 0.5±0.05 MPa, time 10±0.5 min, vacuum degree ≤100 Pa, and thickness 200±10 μm.
3. The preparation method according to claim 1, characterized in that The transition layer in step ④ is specifically an acrylic adhesive, and the spraying process is a pressure of 0.18-0.22 MPa, a distance of 18-20 cm, a thickness of 10±1 nm, and finally cured at room temperature for 23-25 hours.
4. The preparation method according to claim 1, characterized in that The coverage of the nanosilver island structure in step ⑤ is 40-50%, and the thickness is 50±5 nm.
5. The preparation method according to claim 1, characterized in that The second PVDF layer in step ⑤ is doped with 0.5% antioxidant, and the antioxidant is selected from Irganox 1010 or its derivatives.
6. A flexible photovoltaic glass with high flexibility and low reflection, characterized in that: Prepared by the method according to any one of claims 1-5, the structure thereof comprises in sequence: a flexible glass substrate, a perovskite active layer, a transparent conductive layer, an EVA encapsulation layer, a transition layer, a SiO2 inorganic coating and a "PVDF / Ag / PVDF" sandwich structure.
Citation Information
Cited By
Cooling greenhouse for summer planting
CN120323241A
Optical module coating and preparation process thereof
CN120796913A
